Pelatihan Pembuatan Peraturan Desa Melalui Kukerta MBKM Desa Muara Takus - Andrikasmi, Sukamariko; Nduru, Yumaiman; Sari, Tiara Wulan; Sukma, Aisyah Wahyu; Simanjuntak, Paulina; Lauja, Akrima; Azkiannisa, Rifa C.; Chua, Wesley; Maulana, Rizky; Saragih, Varenka Y.P; Sabila, Delfia Rezky; Octaviani, Wanda Tri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The training on Village Regulation (Perdes) drafting through the Independent Campus Community Service Program (Kuliah Kerja Nyata Merdeka Belajar Kampus Merdeka - Kukerta MBKM) in Muara Takus Village was conducted with the aim of enhancing the capacity of village officials in understanding, drafting, and enacting village regulations that align with community needs and are based on applicable laws. Village regulations play a strategic role in governing various aspects of village administration, including governance management, development, community empowerment, and local potential management. However, many village officials still face difficulties in formulating Perdes in accordance with legal principles due to limited understanding of both the substance and the technical drafting of regulatory texts. Using a participatory approach, this training activity was carried out through legal counseling methods, interactive discussions, Perdes draft simulations, and guidance in formulating relevant content based on the needs of the Muara Takus community, such as natural resource management, environmental conservation, and strengthening village institutions. The activity involved 20 village officials and 11 student facilitators, with results showing an 85% increase in understanding of the legal basis, drafting procedures, and mechanisms for establishing Perdes based on pre- and post-training evaluations. Additionally, the activity produced two Perdes drafts focused on new residents who must report and parking retribution at the Muara Takus Village market. This Kukerta MBKM program not only serves as a means for students to contribute to the community but also provides a tangible contribution to strengthening village governance, increasing community participation, and promoting independence, democracy, and justice at the village level.